2005
DOI: 10.1146/annurev.arplant.56.032604.144052
|View full text |Cite
|
Sign up to set email alerts
|

CO2 CONCENTRATING MECHANISMS IN ALGAE: Mechanisms, Environmental Modulation, and Evolution

Abstract: The evolution of organisms capable of oxygenic photosynthesis paralleled a long-term reduction in atmospheric CO2 and the increase in O2. Consequently, the competition between O2 and CO2 for the active sites of RUBISCO became more and more restrictive to the rate of photosynthesis. In coping with this situation, many algae and some higher plants acquired mechanisms that use energy to increase the CO2 concentrations (CO2 concentrating mechanisms, CCMs) in the proximity of RUBISCO. A number of CCM variants are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
1,149
3
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,308 publications
(1,176 citation statements)
references
References 210 publications
16
1,149
3
8
Order By: Relevance
“…Most macroalgae have CO 2 concentrating mechanisms (CCMs), which reduce their dependency on ambient CO 2 (or HCO 3 -) concentrations. Therefore, these taxa have been assumed to be largely insensitive to acidification (Giordano et al 2005). There are no published results for the effects of ocean acidification on Baltic Sea macroalgae, but recent work elsewhere confirms that species with CCMs are likely to be unaffected by, or may benefit marginally from, ocean acidification (Hepburn et al 2011).…”
Section: Primary Producersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most macroalgae have CO 2 concentrating mechanisms (CCMs), which reduce their dependency on ambient CO 2 (or HCO 3 -) concentrations. Therefore, these taxa have been assumed to be largely insensitive to acidification (Giordano et al 2005). There are no published results for the effects of ocean acidification on Baltic Sea macroalgae, but recent work elsewhere confirms that species with CCMs are likely to be unaffected by, or may benefit marginally from, ocean acidification (Hepburn et al 2011).…”
Section: Primary Producersmentioning
confidence: 99%
“…Here again, relatively little work has been done on Baltic Sea species or populations. The prevalence of CCMs in phytoplankton has been suggested as a reason to expect reduced sensitivity to ocean acidification (Giordano et al 2005;Hopkinson et al 2011). For spring bloom species, recent results for the diatom Skeletonema marinoi from the Skagerrak showed that the effects of ocean acidification on growth rate differed between strains and populations but overall, growth of S. marinoi was not affected by increased pCO 2 (750 latm; Kremp et al unpublished results).…”
Section: Primary Producersmentioning
confidence: 99%
“…All cyanobacterial species investigated to date, however, possess mechanisms to enhance the carboxylation efficiency of their RubisCO, reducing the risk of carbon limitation. These processes are commonly referred to as CO 2 concentrating mechanisms (CCMs; Badger et al 2006;Giordano et al 2005;Kaplan and Reinhold 1999). Although CCM functioning should significantly repress the oxygenase function of RubisCO (Colman 1989), photorespiration has recently been found to occur under certain conditions in Synechocystis PCC6803 (Eisenhut et al 2008).…”
Section: Inorganic Carbon Acquisitionmentioning
confidence: 99%
“…CO 2 is the product of all decarboxylase reactions examined so far, including those which operate in vivo close to equilibrium and which can also function as carboxylases. Those carboxylases which are essentially irreversible in vivo can, depending on the enzyme involved, use either CO 2 or HCO 3 − [1]. These carboxylation and decarboxylation reactions are major links in the biogeochemical cycle of carbon, each accounting for a global flux of at least 10 Pmol (10 15 mol) of carbon each year [1].…”
mentioning
confidence: 99%
“…These carboxylation and decarboxylation reactions are major links in the biogeochemical cycle of carbon, each accounting for a global flux of at least 10 Pmol (10 15 mol) of carbon each year [1]. A group of enzyme which can react with both CO 2 and HCO 3 − are the polyphyletic carbonic anhydrases (EC 4.2.1.1) which catalyse the interconversion of CO 2 and HCO 3 − ; the uncatalysed reaction is frequently slow relative to metabolic fluxes of the inorganic carbon species [1].…”
mentioning
confidence: 99%